2007
DOI: 10.1074/jbc.m703330200
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Is Important for Fatty Acid and Cholesterol Uptake by the Proximal but Not Distal Intestine

Abstract: CD36, a membrane protein that facilitates fatty acid uptake, is highly expressed in the intestine on the luminal surface of enterocytes. Cd36 null (Cd36 ؊/؊ ) mice exhibit impaired chylomicron secretion but no overall lipid absorption defect. Because chylomicron production is most efficient proximally we examined whether CD36 function is important for proximal lipid absorption. CD36 levels followed a steep decreasing gradient along three equal-length, proximal to distal intestinal segments (S1-S3). Enterocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
236
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(250 citation statements)
references
References 68 publications
9
236
1
4
Order By: Relevance
“…We utilized this technique to further show that the net absorption of long chain FAs in mice maintained on a high-fat diet is also normal. These data appear to contrast our recent finding that the intestinal absorption of 18:1 is delayed (but not reduced) in CD36-deficient mice following an acute, intragastric bolus of triacylglycerols enriched in triolein (21). The shorter time period (90 min) used in this triolein study versus 24 h for the fecal dual isotope recovery used in the present work is the primary difference likely leading to the disparate results.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…We utilized this technique to further show that the net absorption of long chain FAs in mice maintained on a high-fat diet is also normal. These data appear to contrast our recent finding that the intestinal absorption of 18:1 is delayed (but not reduced) in CD36-deficient mice following an acute, intragastric bolus of triacylglycerols enriched in triolein (21). The shorter time period (90 min) used in this triolein study versus 24 h for the fecal dual isotope recovery used in the present work is the primary difference likely leading to the disparate results.…”
Section: Discussioncontrasting
confidence: 56%
“…We and others (8,21,27) have previously reported that the net absorption of long chain FAs is normal in CD36-deficient mice. Here, we confirm these data using the fecal dual isotope recovery method that is more precise than the indirect methods used previously.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The former mediates cholesterol uptake, and the latter mediates excretion of excessive cholesterol into the intestinal lumen (22,23). CD36 also participates in cholesterol uptake at the brush border of enterocytes (24,25). Three proteins, namely CD36 (25), plasma membrane-associated fatty acidbinding protein (26), and FATP4 (27), are involved in free fatty acid uptake by enterocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Both exogenous OEA administration (18) and endogenous OEA overproduction (present results) stimulate expression of the PPAR-␣-regulated protein CD36. This multifunctional cell-membrane glycoprotein is highly expressed in the small intestine and has been implicated in the transport of fatty acids across the enterocyte membrane (7,12), confirming the suggestion that OEA signaling at PPAR-␣ regulates lipid absorption along with food intake (25). A final consideration is the time course of the anorexic effects of OEA overproduction.…”
Section: Discussionmentioning
confidence: 99%